House Prices and School Quality: The Impact of Score and Non-score Components of Contextual Value-Added - Andreou, Sofia N.; Pashardes, Panos (My University, 2010)
This paper investigates how the newly introduced Contextual Value Added (CVA) indicator of school quality affects house prices in the catchment area of primary and secondary schools in England. The empirical analysis, based on data drawn from three independent and previously unexplored UK data sources, shows that the score component of CVA has a strong positive effect on house prices at both primary and secondary levels of education; while the non-score component of this school quality indicator has a significant (negative) effect only in the analysis of secondary school data. Nevertheless, the effect of CVA and its score and non-score components on house prices also varies with the level of spatial aggregation at which empirical investigation is pursued, assuming a more ‘positive’ role between rather than within Local Authorities (LAs). This reflects the emphasis placed by CVA on ‘public good’ aspects of school quality and suggests that LA policies aimed at raising the average non-score quality characteristics of schools conform to household preferences.
Keywords: School Quality; House Prices; Hedonic Regression